Pengaruh direct labor dan direct material terhadap finished goods sub sektor kosmetik dan peralatan rumah tangga tahun 2017-2020 - Mangowal, Kairin Carol; Siagian, Valentine (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the impact of direct labor and direct materials on the finished goods of manufacturing companies in the cosmetics and household appliances sub-sector. Research analysis using multiple linear regression consisting of 5 companies. The research sample was taken from companies that met the research requirements, namely organizations in the sub-sector of cosmetics and household appliances that were listed in 2017-2020, posted annual reports for four consecutive years in this case in the 2017-2020 period, and attached the number of direct labor, direct materials and finished goods in four predetermined periods. Based on the results of the t-test carried out on each variable, it shows that there is a constructive influence between direct labor on finished goods, the effect of direct materials on finished goods and it can be concluded that the cost of direct labor and direct material affects the number of finished goods produced. Through this, it is hoped that the company will be wiser in planning carefully regarding the amount of direct labor and direct materials that will be used to produce finished goods in order to meet market demand for the company's products.